CURABLE ORGANOPOLYSILOXANE COMPOSITION, RELEASE COATING AGENT CONTAINING SAME, AND LAMINATE
By using a combination of high viscosity and low viscosity chain polysiloxane, hydrogen-containing polysiloxane and catalyst, a hardened film with excellent peeling performance is formed, and the problem of poor peeling performance of adhesive substances in the prior art is solved, and the balance of efficient peeling and adhesion is achieved.
Patent Information
- Application Number
- JP2021567642
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-12-25
- Filing Date
- 2020-12-24
- Publication Date
- 2025-04-23
- Estimated Expiration
- 2040-12-24
AI Technical Summary
The prior art is difficult to achieve efficient peeling performance between the adhesive substance and the surface while maintaining the adhesion of the adhesive substance.
Using an absorbable organic polysiloxane composition, the composition comprising a chain polysiloxane with high viscosity, a chain polysiloxane with low viscosity, a polysiloxane with hydrogen silicon and a catalyst, a hardened film with excellent peeling properties is formed by controlling the mass ratio and structural characteristics of the components.
It realizes that the peeling performance between the adhesive substance and the surface is significantly improved without reducing the adhesion of the adhesive substance, and is suitable for various complex application scenarios.
Smart Images

Figure 0007667744000001 
Figure 0007667744000002 
Figure 0007667744000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a curable organopolysiloxane composition, and more particularly to a curable organopolysiloxane composition capable of forming a release coating that forms a cured coating that exhibits extremely excellent release performance without reducing the adhesion to adhesive substances, and to a release coating agent and laminate comprising the same. [Background technology]
[0002] As a silicone composition for forming a releaseable cured coating that forms a cured coating that exhibits excellent release performance against adhesive substances, an addition reaction type organopolysiloxane composition consisting of an alkenyl group-containing organopolysiloxane, an organohydrogenpolysiloxane, and a platinum catalyst, and further containing a reaction inhibitor, has been widely used. In order to improve the performance, Patent Documents 1 to 3 propose a silicone composition for forming a releaseable cured coating that contains an organopolysiloxane that does not contain an alkenyl group, such as dimethylsiloxane gum or a dimethylsiloxane-methylphenylsiloxane copolymer, added to these components. However, these compositions have drawbacks such as a decrease in adhesiveness of adhesive substances and a decrease in printability of the back of the coating due to migration of silicone, and are not necessarily satisfactory depending on the application.
[0003] In order to solve these problems, Patent Document 4 proposes reducing the peel resistance by mixing two types of high molecular weight siloxanes that have a functional group selected from the group consisting of hydroxyl groups, alkenyl groups, and alkyl groups at the molecular chain end and have a viscosity of 500 centistokes or more in a 30% by weight toluene solution at 25°C, but in recent years, the release performance required for the release layer (especially the effect of reducing the peel resistance) has become even more advanced, and there are cases where the required level is not met as a recent release coating agent. In addition, since two types of high molecular weight siloxanes are mixed, the viscosity of the composition is high, and a composition with better handling and workability (handling ability) is required.
[0004] Furthermore, Patent Document 5 proposes a release composition containing a high molecular weight siloxane having a terminal vinyl group and a degree of polymerization of the siloxane unit in the range of 3,000 to 20,000, and a siloxane having a viscosity of 0.1 to 500 Pa s at 25°C. Although it has been confirmed that this composition improves adhesion to substrates, the performance is still insufficient in terms of solving the problem of achieving easy release properties for adhesive substances.
[0005] Furthermore, Patent Document 6 proposes a release composition containing two types of siloxanes, one with a viscosity of 50 to 10,000 mPa s and the other with a viscosity of 100,000 mPa s or more. Although the objective of imparting slip properties to a cured coating is achieved, as with the above, the performance is still insufficient to resolve the problem of achieving easy release properties for adhesive substances. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] Special Publication No. 53-28943 [Patent Document 2] Japanese Patent Application Publication No. 2-145650 [Patent Document 3] Special Publication No. 3-52498 [Patent Document 4] Japanese Patent Application Publication No. 9-125004 [Patent Document 5] JP 2004-190202 A [Patent Document 6] Japanese Patent Publication No. 159480 / 1983 Summary of the Invention [Problem to be solved by the invention]
[0007] The present invention has been made to solve the above problems, and aims to provide a curable organopolysiloxane composition capable of forming a release cured coating that can form a release cured coating that meets the high release performance requirements in recent years and that can simultaneously suppress a decrease in the adhesiveness of adhesive substances. Another aim is to provide uses for the composition, specifically, a release coating agent made from the composition, and a laminate comprising a release layer and an adhesive layer that uses the composition, such as a release adhesive tape / sheet. [Means for solving the problem]
[0008] As a result of extensive investigation, the present inventors have discovered: (A) a linear organopolysiloxane which is liquid-like and has a viscosity of 1,000,000 mPa s or more at 25°C, or which is gum-like and has a plasticity at 25°C, and which has alkenyl groups having 2 to 12 carbon atoms only on the side chains of its molecule; (B) a linear organopolysiloxane which has a viscosity of 1,000 mPa s or less at 25°C and which has alkenyl groups having 2 to 12 carbon atoms only on the side chains of its molecule; (C) an organohydrogenpolysiloxane which has two or more silicon-bonded hydrogen atoms (Si-H) in one molecule; and The present inventors have found that the above-mentioned problems can be solved by using a curable organopolysiloxane composition containing (D) a hydrosilylation reaction catalyst, in which the mass ratio of component (A) to component (B) {(A) / (B)} is in the range of 95 / 5 to 5 / 95, and have arrived at the present invention.
[0009] In the present invention, the plasticity is the plasticity measured by a plasticity meter in accordance with the method specified in JIS K 6249, and specifically, it is the value (unit: mm) when a load of 1 kgf is applied to a 4.2 g spherical sample at 25°C for 3 minutes.
[0010] In the curable organopolysiloxane composition of the present invention, the mass ratio of component (A) to component (B) {(A) / (B)} is preferably in the range of 90 / 10 to 10 / 90. Furthermore, it is particularly preferred that the mass ratio of component (A) to component (B) {(A) / (B)} is in the range of 70 / 30 to 30 / 70, and that the molar ratio of SiH groups in component (C) to the total molar number of alkenyl groups in components (A) and (B) is 0.5 to 5.
[0011] In the curable organopolysiloxane composition of the present invention, components (A) and (B) are preferably linear organopolysiloxanes having alkenyl groups having 4 to 12 carbon atoms only on the side chains of the molecules, the content of vinyl (CH2=CH-) moieties in the alkenyl groups being 0.5 to 3.0 mass%, and the molecular chain terminals being blocked with trialkylsilyl groups.
[0012] In the curable organopolysiloxane composition of the present invention, the organic solvent (E) is an optional component, and the composition may or may not contain an organic solvent. In particular, the composition of the present invention may be in any form, such as a solution or suspension, optionally containing the organic solvent (E), and is particularly preferably a solution.
[0013] The curable organopolysiloxane composition of the present invention may further contain (F) a hydrosilylation reaction inhibitor and / or (G) a photopolymerization initiator.
[0014] The curable organopolysiloxane composition of the present invention can be suitably used as a release coating agent.
[0015] The problems of the present invention are solved by a sheet-like article having a cured layer formed by curing the curable organopolysiloxane composition of the present invention and a sheet-like substrate. In particular, the cured layer is preferably a release cured coating.
[0016] The object of the present invention is also achieved by a laminate having a structure in which a pressure-sensitive adhesive layer is disposed opposite at least one release layer, the release layer being a release layer made of a cured product obtained by curing a release coating agent comprising the curable organopolysiloxane composition of the present invention. Effect of the Invention
[0017] In the release sheet obtained by coating the curable organopolysiloxane composition on a sheet-like substrate, for example, a substrate film, and curing the composition, the release layer made of the composition has excellent release performance against adhesive substances and can suppress the decrease in adhesion of the adhesive substance. Also, a release coating agent made of the composition according to the present invention can be provided. Similarly, a laminate having a release layer and an adhesive layer using the above composition, such as a peelable adhesive tape / sheet, can be provided.
[0018] Specifically, a release sheet obtained by using the curable organopolysiloxane composition of the present invention in a release layer has excellent releasability for the adhesive substance. Specifically, when an adhesive substance is coated on the surface of a cured layer obtained by curing the curable organopolysiloxane composition of the present invention, and the cured layer is dried and cured, the resistance when peeling the release sheet from the coated adhesive substance can be reduced.
[0019] The release sheet having a cured layer obtained by curing the curable organopolysiloxane composition according to the present invention, and the release sheet for adhesive substances according to the present invention are excellent in applicability to plastic films. Specifically, when the release agent composition, which is the curable polyorganosiloxane composition of the present invention, is applied to a plastic film and dried and cured, it can be applied uniformly without causing repelling on the plastic film surface, and a release sheet having a uniform appearance can be obtained.
[0020] Furthermore, the release sheet having a cured layer obtained by curing the curable organopolysiloxane composition according to the present invention is excellent in maintaining the adhesive strength of the adhesive substance. Specifically, after applying an adhesive substance to the surface of the cured layer obtained by curing the curable organopolysiloxane composition according to the present invention, drying and curing the adhesive substance, and peeling off the cured layer (peeling layer) from the applied adhesive substance, the adhesive strength of the adhesive substance is not reduced and can be maintained at the original level. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0021] The curable organopolysiloxane composition of the present invention is (A) a linear organopolysiloxane which is in a liquid state having a viscosity of 1,000,000 mPa s or more at 25°C or in a gum state having a plasticity at 25°C and which has alkenyl groups having 2 to 12 carbon atoms only on the side chains of its molecule; and (B) a linear organopolysiloxane which has a viscosity of 1,000 mPa s or less at 25°C and which has alkenyl groups having 2 to 12 carbon atoms only on the side chains of its molecule. The composition comprises (C) an organohydrogenpolysiloxane having two or more silicon-bonded hydrogen atoms (Si-H) in one molecule, and (D) a hydrosilylation reaction catalyst, the mass ratio of component (A) to component (B) {(A) / (B)} being in the range of 95 / 5 to 5 / 95, and may optionally contain (E) an organic solvent and / or (F) a hydrosilylation reaction inhibitor, and in a particularly preferred embodiment, may contain (G) a photopolymerization initiator. Below, each of the components of the curable organopolysiloxane composition and a release sheet for releasing adhesive substances, which is a release sheet produced using the composition of the present invention, will be described in detail.
[0022] The viscosity of the organopolysiloxane described in this specification at 25° C. is a value measured using a rotational viscometer. The plasticity is a value measured using a plasticity meter in accordance with the method specified in JIS K 6249, specifically, the value (unit: mm) when a load of 1 kgf is applied to a 4.2 g spherical sample for 3 minutes at 25° C.
[0023] [Component (A)] Component (A) in the present invention is an organopolysiloxane or organopolysiloxane mixture with a so-called high degree of polymerization, and the range of its physical properties expands continuously from a high viscosity liquid region to a gum-like region with plasticity as the degree of polymerization increases, etc. In other words, when the viscosity at 25°C exceeds 15,000,000 mPa s as a result of an increase in the degree of polymerization of the organopolysiloxane, it generally becomes difficult to measure the viscosity, and the mixture shifts from a region exhibiting a high viscosity (liquid) to a region whose physical properties are specified by the plasticity (gummy).
[0024] That is, component (A) of the present invention includes organopolysiloxanes or organopolysiloxane mixtures having a degree of polymerization, etc., which allows viscosity measurement at 25°C and which exhibit a liquid state with a viscosity of 1,000,000 mPa·s or more, including a region with an even higher degree of polymerization, and which are difficult to measure viscosity at 25°C, and which reach a region of a degree of polymerization, etc., in which the physical properties must be specified by the plasticity. In particular, the component (A) is preferably an organopolysiloxane or organopolysiloxane mixture that is liquid-like with a viscosity of 1,000,000 mPa·s or more at 25°C or that exhibits a gummy state with a plasticity of 3.0 mm or less at 25°C. Most preferably, the component (A) is an organopolysiloxane or organopolysiloxane mixture that exhibits a gummy state with a plasticity of 0.5 to 3.0 mm at 25°C.
[0025] One of the features of the invention is that component (A) is a linear organopolysiloxane having alkenyl groups with 2 to 12 carbon atoms only on the side chains of the molecule, and does not have reactive functional groups such as alkenyl groups at the molecular chain terminals. If an alkenyl group is present at the molecular chain terminals, it may not be possible to achieve both the technical effects of the invention, namely, high release properties and the effect of preventing a decrease in adhesion to adhesive substances.
[0026] It is preferable that component (A) is a linear organopolysiloxane having alkenyl groups having 2 to 12 carbon atoms only on the side chains of the molecule, the content of vinyl (CH2=CH-) moieties in the alkenyl groups being 0.5 to 3.0 mass%, and the molecular chain terminals being blocked with trialkylsilyl groups.
[0027] More preferably, component (A) is a linear organopolysiloxane having hexenyl groups as alkenyl groups having 2 to 12 carbon atoms only on the side chains of the molecule and both molecular chain terminals blocked with trimethylsiloxy groups. It is particularly preferred that the functional groups other than hexenyl groups in component (A) are substantially only methyl groups or phenyl groups.
[0028] Component (A) can be selected from organopolysiloxanes, branched organopolysiloxanes, and linear or branched organopolysiloxanes containing a partial cyclic structure. From an industrial standpoint, however, it is preferably a linear organopolysiloxane represented by the following chemical formula (1). [ka]
[0029] In formula (1), R 1 R are each independently an unsubstituted or halogen-substituted alkyl group having 1 to 20 carbon atoms (e.g., a methyl group, etc.) or an aryl group having 6 to 22 carbon atoms (e.g., a phenyl group, etc.). 2 are each independently R 1 or a hydroxyl group, R 1 It is preferable that R 3 is an alkenyl group having 2 to 12 carbon atoms. m is a number equal to or greater than 0, n is a number equal to or greater than 1, and m+n is a number within the range in which the organopolysiloxane represented by the above formula (1) is in a liquid state with a viscosity of 1,000,000 mPa s or more at 25°C or in a gum-like state having plasticity at 25°C. Note that m, n, and R 1 , R 2 and R 3is preferably a number such that the content of vinyl (CH2=CH-) moieties in alkenyl groups having 2 to 12 carbon atoms in the organopolysiloxane molecule represented by the above formula (1) is 0.5 to 3.0 mass %.
[0030] For example, R in Eq. (1) 3 is an alkenyl group having 2 to 12 carbon atoms, the content of the vinyl (CH2=CH-) moiety in the alkenyl group is represented by the following formula: (R 3 Molecular weight of the vinyl portion: approx. 27) x m / total molecular weight x 100 (mass%) Component (A) is an organopolysiloxane represented by the above formula (1) that satisfies the condition that the content of vinyl (CH2=CH-) moieties in the alkenyl groups having 2 to 12 carbon atoms is in the range of 0.5 to 3.0 mass%, more preferably in the range of 0.5 to 2.0 mass%.
[0031] If the content of vinyl moieties in the alkenyl group in component (A) is less than the lower limit, the curing reactivity is significantly reduced, and the amount of silicone polymer transferred to the adhesive increases, which may reduce the adhesiveness of the adhesive or make it difficult to peel the release sheet from the adhesive.On the other hand, if the content of vinyl moieties in the alkenyl group exceeds the upper limit, it may become difficult to peel the adhesive from the cured layer.In addition, if the viscosity or plasticity of component (A) is outside the above range, the intended effect of reducing peel resistance of this composition may not be obtained.
[0032] Furthermore, in component (A), m+n in formula (1) is a number ranging from the region in which the organopolysiloxane represented by formula (1) above exhibits a high viscosity liquid state to the region in which it exhibits a gum-like state having plasticity, and is particularly preferably a number that results in a liquid organopolysiloxane having a viscosity of 1,000,000 mPa s or more at 25°C, to a number that results in a gum-like organopolysiloxane having a plasticity of 3.0 mm or less at 25°C.
[0033] More specifically, component (A) is particularly preferably a linear organopolysiloxane represented by the following chemical formula (2), which has hexenyl groups as alkenyl groups having 2 to 12 carbon atoms only on the side chains of the molecule, the content of vinyl (CH2=CH-) moieties in the hexenyl groups being in the range of 0.5 to 3.0 mass%, and both molecular chain terminals being blocked with trimethylsiloxy groups. [ka] (In formula (2), m1 is a number equal to or greater than 0 and n1 is a positive number such that the content of vinyl (CH2=CH-) moieties in the hexenyl group (-(CH2)4CH=CH2) in the molecule represented by formula (2) is in the range of 0.5 to 3.0 mass%, more preferably in the range of 0.5 to 2.0 mass%. Furthermore, m1+n1 is a number within the range from the region in which the organopolysiloxane represented by formula (2) exhibits a high viscosity liquid state to the region in which it exhibits a gummy state having plasticity, and is particularly preferably a number within the range from which the organopolysiloxane exhibits a liquid state having a viscosity of 1,000,000 mPa s or more at 25°C to which the organopolysiloxane exhibits a gummy state having a plasticity of 3.0 mm or less at 25°C.)
[0034] The viscosity of component (A) at 25°C is liquid to gum-like (usually a semi-solid high-polymerization silicone polymer with plasticity and a viscosity of 10,000,000 mPa·s or more). As explained above, the range of physical properties of the high-polymerization organopolysiloxane or organopolysiloxane mixture, which is the preferred component (A) of the present invention, expands continuously from a region exhibiting a high viscosity liquid state to a region exhibiting a plastic gum-like state due to an increase in the degree of polymerization, etc. In other words, when the degree of polymerization of the organopolysiloxane increases, etc., and the viscosity at 25°C exceeds 15,000,000 mPa·s, it generally becomes difficult to measure the viscosity, and the viscosity shifts from a region exhibiting a high viscosity (liquid state) to a region in which the physical properties are specified by the plasticity (gum-like state).
[0035] There is no upper limit to the viscosity of component (A) at 25°C, but to avoid difficulty in handling, it is preferable that the component (A) be in the form of a liquid with a viscosity of 1,000,000 mPa s or more at 25°C or a gum with a plasticity of 3.0 mm or less at 25°C.
[0036] Component (A) may be a mixture of two or more different types of component (A). Even if the organopolysiloxane is a liquid having a viscosity of less than 1,000,000 mPa s at 25° C. or a gum having a plasticity of more than 3.0 mm at 25° C., it may be possible to handle it more conveniently by mixing it with another organopolysiloxane, and such an embodiment is also within the scope of the present invention.
[0037] When component (A) is a mixture of two or more types of organopolysiloxanes and the mixture as a whole is gum-like, it is preferable that its plasticity (measured with a plasticity meter in accordance with the method specified in JIS K 6249: the value when a load of 1 kgf is applied to a 4.2 g spherical sample for 3 minutes at 25°C) is in the range of 0.5 to 10.0 mm, and particularly preferably in the range of 0.5 to 3.0 mm.
[0038] [Component (B)] Component (B) is a liquid with a viscosity of 1,000 mPa s or less at 25°C, and is a linear organopolysiloxane having alkenyl groups with 2 to 12 carbon atoms only on the side chains of the molecule. Component (B) differs significantly from component (A) in terms of viscosity, i.e., degree of siloxane polymerization, but components (A) and (B) have a common structure in that they do not have reactive functional groups such as alkenyl groups at the molecular chain ends, and when alkenyl groups are present at the molecular chain ends, the technical effects of the present invention, that is, high release properties and the effect of preventing a decrease in adhesion to adhesive substances, may not be achieved simultaneously.
[0039] It is preferable that component (B) is a linear organopolysiloxane having alkenyl groups having 2 to 12 carbon atoms only on the side chains of the molecule, the content of vinyl (CH2=CH-) moieties in the alkenyl groups being 0.5 to 3.0 mass%, and the molecular chain terminals being blocked with trialkylsilyl groups.
[0040] Component (B) can be selected from linear organopolysiloxanes, branched organopolysiloxanes, and linear or branched organopolysiloxanes containing a partial cyclic structure. From an industrial standpoint, however, it is preferably a linear organopolysiloxane represented by the following chemical formula (3). [ka]
[0041] In formula (3), R 11 R are each independently an unsubstituted or halogen-substituted alkyl group having 1 to 20 carbon atoms (e.g., a methyl group, etc.) or an aryl group having 6 to 22 carbon atoms (e.g., a phenyl group, etc.). 12 are each independently R 11 or a hydroxyl group, R 11 It is preferable that R 13 is an alkenyl group having 2 to 12 carbon atoms. m' is a number equal to or greater than 0, n' is a number equal to or greater than 1, and m'+n' is a number within the range in which the viscosity of the organopolysiloxane represented by the above formula (3) at 25°C is 1,000 mPa s or less. 11 , R 12 , and R 13 is a number such that the content of vinyl (CH2=CH-) moieties in alkenyl groups having 2 to 12 carbon atoms in the organopolysiloxane molecule represented by the above formula (3) is 0.5 to 3.0 mass %.
[0042] For example, R in Eq. (3) 13 is an alkenyl group having 2 to 12 carbon atoms, the content of the vinyl (CH2=CH-) moiety in the alkenyl group is represented by the following formula: (R 13 Molecular weight of the vinyl portion: approx. 27) x m / total molecular weight x 100 (mass%) Component (B) is an organopolysiloxane that satisfies the condition in the above formula (3) that the content of vinyl (CH2=CH-) moieties in the alkenyl groups having 2 to 12 carbon atoms is in the range of 0.5 to 3.0 mass%, more preferably in the range of 0.5 to 2.0 mass%.
[0043] If the content of vinyl moiety in the alkenyl group in component (B) is less than the above lower limit, the curing reactivity is significantly reduced, and the amount of silicone polymer transferred to the adhesive increases, the adhesiveness of the adhesive decreases, and the peeling of the release sheet from the adhesive may become difficult.On the other hand, if the content of vinyl moiety in the alkenyl group exceeds the above upper limit, the peeling of the adhesive from the peeling layer obtained by curing may become difficult.
[0044] In component (B), m'+n' in formula (3) is in a range in which the organopolysiloxane represented by formula (3) above exhibits a liquid state of 1,000 mPa·s or less at 25°C, and is particularly preferably in the range of 5 to 500 mPa·s. If the viscosity of component (B) exceeds 1,000 mPa·s, the intended effect of reducing peel resistance of the composition may not be achieved, even when used in combination with component (A).
[0045] More specifically, component (B) is particularly preferably a linear organopolysiloxane represented by the following chemical formula (4), which has hexenyl groups as alkenyl groups having 2 to 12 carbon atoms only on the side chains of the molecule, the content of vinyl (CH2=CH-) moieties in the hexenyl groups being in the range of 0.5 to 3.0 mass%, and both molecular chain terminals being blocked with trimethylsiloxy groups.
[0046] [ka] (In formula (4), m1' is a number equal to or greater than 0, n1' is a positive number, and n1' is a number such that the content of vinyl (CH2=CH-) moieties in the hexenyl group (-(CH2)4CH=CH2) in the molecule represented by formula (4) is in the range of 0.5 to 3.0 mass%, more preferably in the range of 0.5 to 2.0 mass%. In addition, m1'+n1' is preferably a number such that the viscosity of the organopolysiloxane represented by formula (4) at 25°C is 1,000 mPa s or less.
[0047] Component (B) may be a mixture of two or more different types of components (B). Note that even organopolysiloxanes with a viscosity at 25°C of more than 1,000 mPa s may be more easily handled when mixed with other organopolysiloxanes, and such embodiments are also within the scope of the present invention.
[0048] When component (B) is a mixture of two or more types of organopolysiloxane, the viscosity of the mixture at 25° C. is no greater than 1,000 mPa·s, and it is particularly preferred that it be in the range of 5 to 500 mPa·s.
[0049] [Mass ratio of component (A) to component (B) {(A) / (B)}] The present invention makes it possible to achieve both excellent release properties and the technical effects of suppressing a decrease in adhesive strength to adhesive substances by combining, in a specific mass ratio range, component (A) and component (B), which have similar siloxane structures but differ greatly in their viscosities (degree of siloxane polymerization).
[0050] Specifically, the mass ratio of component (A) to component (B) {(A) / (B)} is preferably in the range of 95 / 5 to 5 / 95, more preferably in the range of 90 / 10 to 10 / 90, and even more preferably in the range of 70 / 30 to 30 / 70. If the mass ratio (A) / (B) is greater than 95 / 5, the peel resistance is not reduced to a sufficient level, and it may be difficult to peel the release sheet from the adhesive material. If the mass ratio (A) / (B) is less than 5 / 95, it may be difficult to uniformly coat the release sheet on a sheet-like substrate such as a plastic film, and the appearance of the release sheet may be poor.
[0051] [Component (C)] Component (C) is an organohydrogenpolysiloxane having two or more silicon-bonded hydrogen atoms (Si-H) in one molecule, and is a crosslinking agent for the above-mentioned components (A) and (B). Component (C) preferably has at least three silicon-bonded hydrogen atoms in one molecule, and the bonding positions of the hydrogen atoms in the molecule are not particularly limited. In addition, examples of organic groups other than hydrogen atoms that bond to silicon atoms contained in component (C) include alkyl groups such as methyl, ethyl, propyl, butyl, and octyl, and methyl is preferred. In addition, examples of the molecular structure of the organohydrogenpolysiloxane of component (C) include linear, branched, and branched cyclic structures, or a combination of one or more of these. The number of silicon-bonded hydrogen atoms in one molecule is the average value of all molecules.
[0052] The viscosity of component (C) at 25°C is 1 to 1,000 mPa·s, and preferably 5 to 500 mPa·s. If the viscosity of component (C) at 25°C is less than 1 mPa·s, component (C) will be more likely to volatilize from the curable organopolysiloxane composition containing it, whereas if it exceeds 1,000 mPa·s, the curing time of the curable organopolysiloxane composition will be longer.
[0053] Examples of such component (C) include, but are not limited to, dimethylsiloxane-methylhydrogensiloxane copolymers capped at both ends with trimethylsiloxy groups, dimethylsiloxane-methylhydrogensiloxane copolymers capped at both ends with dimethylhydrogensiloxy groups, dimethylpolysiloxanes capped at both ends with dimethylhydrogensiloxy groups, methylhydrogenpolysiloxanes capped at both ends with trimethylsiloxy groups, cyclic methylhydrogenpolysiloxanes, and cyclic methylhydrogensiloxane-dimethylsiloxane copolymers. Component (C) is one type of organohydrogenpolysiloxane or a mixture of two or more types of organohydrogenpolysiloxanes represented by the following general formula (5), and can form a layer of cured organopolysiloxane by addition reaction (hydrosilylation reaction) with the silicon-bonded alkenyl groups contained in components (A) and (B). [ka]
[0054] In formula (5), R 21 R is an unsubstituted or substituted alkyl group or aryl group, and is preferably an alkyl group having 1 to 10 carbon atoms, a halogenated alkyl group having 1 to 10 carbon atoms, or a phenyl group. 22 are each independently R 12 or a hydrogen atom (-H), but when q=0, R 22 is a hydrogen atom (-H). p and q are numbers of 0 or more, and p+q is a number in the range that gives the organopolysiloxane represented by formula (5) above a viscosity of 1 to 1,000 mPa s at 25°C.
[0055] The amount of component (C) in the curable organopolysiloxane composition of the present invention is an amount such that the molar ratio of SiH groups to the total number of moles of alkenyl groups (including vinyl moieties consisting of carbon-carbon double bonds) in components (A) and (B) is 0.5 to 5.0, and preferably 1.0 to 3.0. If this molar ratio is less than the lower limit mentioned above, the curability of the resulting curable organopolysiloxane composition decreases, and if it exceeds the upper limit mentioned above, the peel resistance of the release layer obtained by curing against adhesive substances increases, and there is a risk that practical peelability cannot be obtained.
[0056] [Component (D)] Component (D) is a hydrosilylation catalyst, which promotes the addition reaction (hydrosilylation reaction) between silicon-bonded alkenyl groups present in the curable organopolysiloxane composition and silicon-bonded hydrogen atoms.Preferred hydrosilylation catalysts are those containing platinum metals, and specific examples thereof include platinum chloride, alcohol-modified platinum chloride, olefin complexes of platinum chloride, complexes of platinum chloride and ketones, complexes of platinum chloride and vinylsiloxanes, platinum tetrachloride, platinum fine powder, solid platinum supported on alumina or silica carriers, platinum black, platinum olefin complexes, platinum alkenylsiloxane complexes, platinum carbonyl complexes, and platinum catalysts of thermoplastic organic resin powders such as methyl methacrylate resins, polycarbonate resins, polystyrene resins, and silicone resins containing these platinum catalysts. In particular, platinum alkenylsiloxane complexes such as a complex of chloroplatinic acid and divinyltetramethyldisiloxane, a complex of chloroplatinic acid and tetramethyltetravinylcyclotetrasiloxane, platinum divinyltetramethyldisiloxane complex, and platinum tetramethyltetravinylcyclotetrasiloxane complex are preferably used.
[0057] The amount of component (D) added to the curable organopolysiloxane composition may be any catalytic amount, and typically, the amount of component (D) is preferably such that the amount of platinum-based metal contained in component (D) is in the range of 1 to 1,000 ppm, and more preferably 5 to 500 ppm, relative to the total amount of components (A) to (C) in the curable organopolysiloxane composition of the present invention.
[0058] [Other components (E) to (G) and overall viscosity of the composition] The curable organopolysiloxane composition according to the present invention may optionally contain an organic solvent (E). In particular, since the curable organopolysiloxane composition according to the present invention has a high content of component (A), it is preferable to use a composition containing components (A) to (D) by dispersing or dissolving it in a known organic solvent (E) in order to improve handling, workability and coatability. However, as long as it does not go against the object of the present invention, it is also possible to use the above-mentioned components (A) to (D) by dispersing or dissolving them in a low-viscosity liquid organopolysiloxane other than any organic solvent (for example, a linear or cyclic organopolysiloxane having a low viscosity of about 0.5 to 10 mPa·s at 25°C). Examples of organic solvents include aromatic hydrocarbon solvents such as toluene and xylene, aliphatic hydrocarbon solvents such as hexane, octane, and isoparaffin, ketone solvents such as acetone, methyl ethyl ketone, and methyl isobutyl ketone, ester solvents such as ethyl acetate and isobutyl acetate, ether solvents such as diisopropyl ether and 1,4-dioxane, cyclic polysiloxanes having a polymerization degree of 3 to 6 such as hexamethylcyclotrisiloxane, octamethylcyclotetrasiloxane, and decamethylcyclopentasiloxane, and halogenated hydrocarbons such as trichloroethylene, perchloroethylene, trifluoromethylbenzene, 1,3-bis(trifluoromethyl)benzene, and methylpentafluorobenzene. When the curable organopolysiloxane composition of the present invention is thinly coated on a sheet-like substrate such as polyolefin having low heat resistance, it is preferable to use aromatic hydrocarbon solvents such as toluene and xylene because they have little effect on the curability of the composition.
[0059] In addition to the above-mentioned components (A) to (D) and optionally component (E), the curable organopolysiloxane composition of the present invention preferably further contains (F) a hydrosilylation reaction inhibitor in order to inhibit gelation and curing at room temperature to improve storage stability and to render the composition curable when heated. Examples of hydrosilylation reaction inhibitors include acetylene compounds, enyne compounds, organic nitrogen compounds, organic phosphorus compounds, and oxime compounds. Specific examples of the compounds include alkyne alcohols such as 2-methyl-3-butyn-2-ol, 3,5-dimethyl-1-hexyn-3-ol, 3-methyl-1-pentyn-3-ol, 2-phenyl-3-butyn-2-ol, and 1-ethynyl-1-cyclohexanol (ETCH); 3-methyl-3-trimethylsiloxy-1-butyne, 3-methyl-3-trimethylsiloxy-1-pentyne, 3,5-dimethyl-3-trimethylsiloxy-1-hexyne, 3-methyl ... Examples include ene-yne compounds such as methyl-3-penten-1-yne and 3,5-dimethyl-3-hexen-1-yne; and alkenyl siloxanes such as 1-ethynyl-1-trimethylsiloxycyclohexane, bis(2,2-dimethyl-3-butynoxy)dimethylsilane, 1,3,5,7-tetramethyl-1,3,5,7-tetravinylcyclotetrasiloxane, and 1,3,5,7-tetramethyl-1,3,5,7-tetrahexenylcyclotetrasiloxane.
[0060] The amount of hydrosilylation reaction inhibitor (F) added to the curable organopolysiloxane composition is usually within the range of 0.001 to 5 parts by mass of component (F) per 100 parts by mass of component (A); however, the preferred amount of component (F) can be easily determined appropriately depending on the type of component (F), the characteristics and amount of hydrosilylation reaction catalyst used, the content of C2 to C12 alkenyl groups in components (A) and (B), the amount of silicon-bonded hydrogen atoms in component (C), and the desired pot life and working environment for the curable composition.
[0061] The curable organopolysiloxane composition of the present invention contains the above-mentioned components (A) to (D), optionally component (E), and further component (F), and is capable of forming a cured coating having excellent release properties by carrying out an addition reaction in the presence of a hydrosilylation reaction catalyst (D) at room temperature or at a temperature of 50 to 200°C.
[0062] Furthermore, since the physical properties and releasability of the resulting cured film are excellent, it is preferable to cure the curable organopolysiloxane composition of the present invention by energy rays (also called actinic rays), such as ultraviolet rays or electron beams, particularly ultraviolet rays. In this case, ultraviolet curing can be performed by only ultraviolet curing or by a combination of ultraviolet curing and heat curing. The curing time of the curable composition can be appropriately adjusted depending on the curing conditions used. In order to impart good ultraviolet curing properties to the curable organopolysiloxane composition of the present invention, it is preferable to further add a photopolymerization initiator (G) to the composition. The component (G) will be described below.
[0063] The (G) photopolymerization initiator is a component that gives the curable organopolysiloxane composition of the present invention ultraviolet curability, and by using both heat curing by addition reaction and ultraviolet curing, the heat damage to the plastic film substrate with low heat resistance is reduced, and the adhesiveness of the cured product of the present invention to the plastic film is improved. Furthermore, the silicone component is prevented from migrating from the surface of the cured film made of the cured composition of the present invention onto the sheet, and the sheet is prevented from being contaminated by the silicone component (this is called silicone migration), and the silicone migration can be further reduced. This (G) component can be appropriately selected from known compounds that generate radicals when irradiated with ultraviolet light, such as organic peroxides, carbonyl compounds, organic sulfur compounds, and azo compounds. Specific compounds include acetophenone, propiophenone, benzophenone, xanthol, fluorene, benzaldehyde, anthraquinone, triphenylamine, 4-methylacetophenone, 3-pentylacetophenone, 4-methoxyacetophenone, 3-bromoacetophenone, 4-allylacetophenone, p-diacetylbenzene, 3-methoxybenzophenone, 4-methylbenzophenone, 4-chlorobenzophenone, 4,4-dimethoxybenzophenone, 4-chloro-4-benzylbenzophenone, 3-chloro Examples of the component (G) include xanthone, 3,9-dichloroxanthone, 3-chloro-8-nonylxanthone, benzoin, benzoin methyl ether, benzoin butyl ether, bis(4-dimethylaminophenyl)ketone, benzyl methoxyketal, 2-chlorothioxanthone, diethylacetophenone, 1-hydroxycyclohexyl phenyl ketone, 2-methyl[4-(methylthio)phenyl]2-morpholino-1-propanone, 2,2-dimethoxy-2-phenylacetophenone, and diethoxyacetophenone. When the composition of the present invention is cured by ultraviolet light, preferred components (G) are benzophenone, 4-methoxyacetophenone, 4-methylbenzophenone, diethoxyacetophenone, and 1-hydroxycyclohexyl phenyl ketone.Particularly preferred components (G) include diethoxyacetophenone and 1-hydroxycyclohexyl phenyl ketone.
[0064] The photopolymerization initiator (G) may be used alone or in combination of two or more. The amount of the photopolymerization initiator is not particularly limited, but is in the range of 0.01 to 10 parts by mass, and preferably in the range of 0.01 to 2.5 parts by mass, per 100 parts by mass of component (A). When the amount of component (G) is within the above range, the release cured coating obtained by curing the composition of the present invention has improved silicone migration and excellent physical properties such as strength.
[0065] The curable organopolysiloxane composition of the present invention is suitable for use as a solution-type curable organopolysiloxane composition containing an organic solvent (E). In particular, in order to obtain good coating properties of the composition onto a sheet-like substrate, the curable organopolysiloxane composition of the present invention preferably has a viscosity of the entire composition at 25°C in the range of 100 to 100,000 mPa·s, and more preferably has a viscosity of 100 to 50,000 mPa·s.
[0066] [Other optional ingredients] In addition to the above components, the curable organopolysiloxane composition of the present invention can further contain other optional components.The other optional components include, for example, adhesion promoters made of alkoxysilane compounds such as 3-glycidoxypropyltrimethoxysilane and 3-methacryloxypropyltrimethoxysilane; antioxidants such as phenols, quinones, amines, phosphorus, phosphite, sulfur, and thioethers; light stabilizers such as triazoles and benzophenones; flame retardants such as phosphates, halogens, phosphorus, and antimony; one or more surfactants selected from cationic surfactants, anionic surfactants, and nonionic surfactants; known additives such as antistatic agents, heat resistance agents, dyes, and pigments, and one or more of the components selected from these can be added to the curable organopolysiloxane composition of the present invention in combination.
[0067] [Method of producing the composition] The composition of the present invention can be produced by homogeneously mixing the above-mentioned components (A) to (D), and optionally the components (E), (F), and (G), and other optional components. The order of addition of each component is not particularly limited, but if the composition obtained after mixing is not used immediately, it is preferable to store the mixture of components (A), (B), and (C) separately from component (D), and mix both immediately before use. In addition, in a composition consisting of components (A) to (D) and optionally other components such as component (E), a composition in which the type and amount of (F) hydrosilylation reaction inhibitor is adjusted so that the composition does not crosslink at room temperature but crosslinks and hardens when heated is also preferable.
[0068] [Use of the composition: release coatings and release sheets] The curable organopolysiloxane composition of the present invention can be suitably used as a release coating agent. When the composition is uniformly applied to a sheet-like substrate, and heated, irradiated with energy rays (e.g., ultraviolet rays, electron beams, etc.) or a combination of these is used under conditions sufficient for components (A) to (C) to undergo a hydrosilylation reaction and crosslink, a release sheet having a release layer made of a cured silicone coating (i.e., a cured organopolysiloxane) coating on the surface of the sheet-like substrate is obtained. The release sheet according to the present invention has the characteristics that the adhesive substance can be applied well onto the cured silicone coating, the adhesive substance after drying can be easily peeled off from the substrate, and the adhesiveness and adhesive force of the adhesive substance are not reduced. That is, the release sheet of the present invention obtained in this manner can be suitably used as a release sheet for adhesive substances. In addition, the cured layer obtained by curing the curable composition of the present invention has excellent flexibility, and therefore has the advantage of good conformability to the substrate and little entrapment of air bubbles when applied to a non-flat object. For this reason, it can be extremely suitably used in applications requiring both release properties of the cured layer and adhesion properties of the cured layer to the object to be protected, such as protective films for optical displays and glass surfaces.
[0069] The sheet-like substrate for coating the curable polyorganosiloxane composition of the present invention is not particularly limited, and any of the conventionally known materials can be appropriately selected and used. Examples of such substrates include films made of plastics such as polyesters such as polyethylene terephthalate and polyethylene naphthalate; polyolefins such as polypropylene and polymethylpentene; polycarbonate; and polyvinyl acetate. The film may be a single layer, or may be composed of two or more layers made of the same or different plastics. As the sheet-like substrate used in the present invention, plastic films, particularly polyester films, are preferred, and polyethylene terephthalate films are particularly preferred. Among these, it is preferable to use biaxially oriented polyethylene terephthalate films as the sheet-like substrate. Polyethylene terephthalate films are less likely to generate dust during processing, use, etc. Therefore, it is possible to effectively prevent poor coating of adhesive substances on sheet-like substrates caused by dust, etc. In addition, antistatic treatment of polyethylene terephthalate films and use of the same as sheet-like substrates is also effective in preventing poor coating of adhesive substances on sheet-like substrates.
[0070] In addition, in order to improve the adhesion between the curable organopolysiloxane of the present invention applied to the surface of the sheet-like substrate and the surface of the sheet-like substrate, if desired, one or both sides of the sheet-like substrate can be subjected to a surface treatment such as an oxidation method or a roughening method, or a primer treatment. Examples of the oxidation method include corona discharge treatment, plasma discharge treatment, chromium oxidation treatment (wet), flame treatment, hot air treatment, ozone treatment, and ultraviolet irradiation treatment, and examples of the roughening method include sandblasting and thermal spraying treatment. Among these surface treatment methods, a suitable method can be selected according to the type of sheet-like substrate, but the corona discharge treatment method is a preferred method because the desired effect obtained by the surface treatment of the sheet-like substrate is high and the operation is simple.
[0071] The thickness of the sheet-like substrate is generally from 10 to 300 μm, preferably from 15 to 200 μm, and particularly preferably from 20 to 125 μm.
[0072] The method for applying the curable organopolysiloxane composition of the present invention onto a sheet-like substrate can be any known method, such as gravure coating, bar coating, spray coating, spin coating, knife coating, roll coating, and die coating.
[0073] When the curable organopolysiloxane composition of the present invention is applied to a sheet-like substrate and cured, the thickness of the layer of the cured organopolysiloxane composition is not particularly limited, but is preferably 0.01 to 3 μm, more preferably 0.03 to 1 μm. If the thickness of the layer of the cured organopolysiloxane composition on the sheet-like substrate is less than 0.01 μm, when the layer is used as a release sheet for adhesive substances, the layer may not function sufficiently as a release agent layer. On the other hand, if the thickness of the layer of the cured organopolysiloxane composition on the sheet-like substrate exceeds 3 μm, blocking may occur when the resulting release sheet is wound into a roll. Furthermore, in addition to the above-mentioned antistatic layer, other layers may be optionally provided on the surface of the sheet-like substrate opposite to the layer of the cured organopolysiloxane composition, or between the sheet-like substrate and the layer of the organopolysiloxane composition.
[0074] [Laminate] The curable organopolysiloxane composition of the present invention can be used as a release layer-forming organopolysiloxane composition (= release coating agent) used to form a release layer during the production of a release laminate, such as a pressure-sensitive adhesive sheet. Specifically, the laminate of the present invention is a laminate having a structure in which an adhesive layer is arranged opposite to at least one release layer, and the release layer is a release layer made of a cured product obtained by curing the release coating agent of the present invention. Here, the release layer is preferably formed on a sheet-like substrate, and the composition of the present invention is suitable for use as a release sheet for adhesive substances having a sheet-like substrate and a cured layer obtained by applying the curable organopolysiloxane composition of the present invention thereon and curing it, and this release sheet for adhesive substances is suitable for forming an adhesive substance laminate containing an adhesive substance and the release sheet for adhesive substances.
[0075] This adhesive laminate can be prepared by a method including a step of coating an adhesive on the release sheet for adhesive of the present invention, i.e., on the side of the cured polyorganosiloxane composition, and drying / curing the adhesive. More specifically, an adhesive laminate is formed by coating an adhesive on the surface of the layer of the cured organopolysiloxane composition formed on the release sheet for adhesive of the present invention using any coating method, for example, a slot die coating method or a doctor blade method, and further drying / curing the adhesive. Thereafter, it is optional to attach a sheet-like substrate coated with the curable organopolysiloxane composition of the present invention or not coated to the adhesive layer. The release sheet for adhesive of the present invention has excellent peelability from such an adhesive laminate, and can be peeled from the adhesive layer with a low peeling force without causing defects such as breakage of the adhesive. In addition, as described above, the curable organopolysiloxane composition of the present invention has the characteristic of not reducing the adhesion and adhesive force of the adhesive layer made of the adhesive.
[0076] As another embodiment of the adhesive laminate, it can be produced by a method including a step of drying / curing an adhesive substance on a sheet-like substrate not coated with the curable organopolysiloxane composition of the present invention, and then laminating the release sheet for adhesive substances of the present invention onto the adhesive substance. Even in this embodiment, the release sheet for adhesive substances of the present invention has excellent releasability from such an adhesive substance laminate, can be peeled from the adhesive substance layer with a low peeling force without causing defects such as breakage of the adhesive substance, and has the characteristic of not reducing the adhesion and adhesive strength of the adhesive layer.
[0077] As described above, the curable organopolysiloxane composition of the present invention is suitable for use as a release sheet for adhesive substances, but the use is not limited thereto, and it can be used for the surface treatment of various films and sheets. In particular, a release sheet having a cured layer made of the composition of the present invention can be used as a surface protection film for protecting the surfaces of optical parts such as liquid crystal panels, plasma displays, polarizing plates and retardation plates, or electric and electronic parts such as printed wiring boards, ICs, transistors and capacitors, and in this case, it is preferable to add an antistatic agent to the composition of the present invention.
[0078] The antistatic agent may be any known ionic or nonionic antistatic agent without any particular limitation, and examples thereof include a method of adding a silicone oil having a hydrophilic group as the main component (JP Patent Publication 52-103499), a method of adding a sulfonate (JP Patent Publication 3-59096), a method of adding a fluorine-containing silicone oil (JP Patent Publication 1-83085, 1-83086, 1-121390), a method of adding a silicone oil containing a surfactant (JP Patent Publication 1-294099), a method of adding a conductive powder (JP Patent Publication 2-69763, 3-292180, 4-86765), etc. In particular, from the viewpoint of compatibility with the curable organopolysiloxane composition of the present invention, it is preferable to use an antistatic agent that is a lithium salt or a polyether-modified polysiloxane. As these ionic antistatic agents or polyether-modified polysiloxanes, for example, those disclosed in JP-A-2009-30028, JP-A-2012-157978, and JP-A-2011-178828 can be used without particular restrictions. From the viewpoint of antistatic properties, in addition to using the above-mentioned antistatic agents as additives, treatment with antistatic agents such as surfactant-based, silicone-based, organoboron-based, conductive polymer-based, metal oxide-based, and vapor-deposited metal-based agents may also be performed. EXAMPLES
[0079] The present invention will be described in more detail below with examples and comparative examples, but the present invention is not limited to the following examples. In the following examples, "parts" indicating the amount means parts by mass, and the vinyl (CH2=CH-) portion represents the vinyl (CH2=CH-) group portion in the alkenyl group bonded to the silicon atom, and the content of the vinyl portion in the entire molecular weight is expressed in mass%, and when the alkenyl group is a vinyl group, it is simply called "vinyl group content". Viscosity and plasticity are values measured at 25°C. The method for measuring plasticity is as described above, and the viscosity was measured using a digital display B-type rotational viscometer (Vismetron VDA2 type manufactured by Shibaura Systems Co., Ltd.).
[0080] [How to create a release sheet] The curable organopolysiloxane composition was applied to the surface of a biaxially stretched polyester film (Mitsubishi Plastics, thickness 38 μm) using a Mayer bar in an amount equivalent to 0.15 g / m2 in terms of solid content excluding the solvent. After application, the substrate coated with the composition was heat-treated in a hot air circulation oven at 120°C for 30 seconds to form a cured layer of organopolysiloxane on the surface of the polyester film substrate, and the substrate was stored in air at a temperature of 25°C and a humidity of 60% for 72 hours to obtain a release sheet.
[0081] [Coatability evaluation] The release sheets were visually inspected for uniformity of the coating surface. Those with a uniform appearance were rated as acceptable, and those with an uneven appearance were rated as unacceptable.
[0082] [Adhesive substance peel resistance measurement] TESA 7475 adhesive tape was attached to the release sheet and applied with a pressure of 20 g / cm 2 A load of 10 ...
[0083] [Residual adhesion rate measurement] Adhesive tape No. 31B manufactured by Nitto Denko Corporation was attached to the release sheet and applied with a pressure of 20 g / cm 2 The adhesive tape was then peeled off, and the peeled adhesive tape was attached to a stainless steel plate and subjected to a load of 20 g / cm 2After applying a load of 1000 g and leaving the tape in air at 25°C and 60% humidity for 30 minutes, the adhesive tape was pulled at an angle of 180° and a peeling speed of 0.3 m / min using a tensile tester [Tensilon universal tester manufactured by A&D Co., Ltd.], and the force required for peeling (gf1) was measured. In addition, as a blank test, the above tape was attached to a Teflon (registered trademark) sheet in the same manner as above, and the force required for peeling the adhesive tape (gf2) was measured in the same manner as above. From these values, the residual adhesion rate (%) was calculated according to the following formula. Residual adhesion rate (%)=(gf1 / gf2)×100 A residual adhesion rate of 95% or more was considered to be acceptable, and a rate of less than 95% was considered to be unacceptable.
[0084] [Example 1] Composition 1 A solvent-containing curable organopolysiloxane composition (composition 1-1) was obtained by uniformly mixing 66.7 parts of (A) (a-1) polydimethylsiloxane whose molecular chain ends are blocked with methyl groups and which has hexenyl groups on the side chains (plasticity 1.15, content of vinyl (CH2=CH-) moieties in the hexenyl groups 0.80% by mass), 33.3 parts of (B) (b-1) dimethylsiloxane whose molecular chain ends are blocked with methyl groups and which has hexenyl groups on the side chains (viscosity 350 mPa s, vinyl group content 1.20% by mass), (C) a dimethylmethylhydrogenpolysiloxane whose molecular chain ends are blocked with trimethylsiloxy groups on both molecular chain ends and has a viscosity of 25 mPa s in an amount such that the SiH / Vi ratio in the total composition was 1.2, (E) 100.0 parts of toluene, and (F) 1.5 parts of 3-methyl-1-butyn-3-ol. The resulting organopolysiloxane composition was then diluted with (E) a 50 / 50 weight% mixture of toluene and hexane to a solids concentration of 5.0 mass%, and (D) a chloroplatinic acid·1,3-divinyl-1,1,3,3-tetramethyldisiloxane complex was added in an amount such that the amount of platinum metal was 200 ppm relative to the total amount of components (A) to (C), and a release sheet was obtained using the method described above. The appearance of the release sheet thus obtained was observed, and the release force and residual adhesion rate were evaluated. The results are shown in Table 1.
[0085] [Example 2] Composition 2 Composition 2 was obtained in the same manner as in Example 1, except that the amount of component (A) used in Example 1 was changed to 50.0 parts and the amount of component (B) used was changed to 50.0 parts. The appearance of the release sheet thus obtained was observed, and the peel strength and residual adhesion rate were evaluated. These are shown in Table 1.
[0086] [Example 3] Composition 3 Composition 3 was obtained in the same manner as in Example 1, except that the amount of component (A) used in Example 1 was changed to 33.3 parts and the amount of component (B) used was changed to 66.7 parts. The appearance of the release sheet thus obtained was observed, and the peel strength and residual adhesion rate were evaluated. These are shown in Table 1.
[0087] [Comparative Example 1] Comparative Composition 1 Comparative composition 1 was obtained in the same manner as in Example 1, except that the component (B) in Example 1 was not used, and the amount of component (A) used was changed to 100.0 parts, the amount of component (E) used to 333.3 parts, and the amount of component (F) used to 0.9 parts. The appearance of the release sheet thus obtained was observed, and the peel strength and residual adhesion rate were evaluated. These are shown in Table 1.
[0088] [Comparative Example 2] Comparative Composition 2 Composition 2 was obtained in the same manner as in Example 1, except that component (A) in Example 1 was not used and the amount of component (B) used was changed to 100.0 parts. The appearance of the release sheet thus obtained was observed, and the peel strength and residual adhesion rate were evaluated. These are shown in Table 1.
[0089] [Comparative Example 3] Comparative Composition 3 Comparative composition 3 was obtained in the same manner as in Example 1, except that 66.7 parts of (a-2) polydimethylsiloxane (plasticity 1.50, vinyl content 0.75% by mass) in which both molecular chain terminals are blocked with vinyl groups and which has vinyl groups on its side chains was used as component (A) of composition 1 in Example 1. The appearance of the release sheet thus obtained was observed, and the peel strength and residual adhesion rate were evaluated. These are shown in Table 1.
[0090] [Comparative Example 4] Comparative Composition 4 Comparative composition 4 was obtained in the same manner as in Example 1, except that the amount of component (A) used in Comparative composition 3 of Comparative Example 3 was changed to 50.0 parts and the amount of component (B) used was changed to 50.0 parts. The appearance of the release sheet thus obtained was observed, and the peel strength and residual adhesion rate were evaluated. These are shown in Table 1.
[0091] [Comparative Example 5] Comparative Composition 5 Comparative composition 5 was obtained in the same manner as in Example 1, except that the amount of component (A) in Comparative composition 3 of Comparative Example 3 was changed to 33.3 parts and the amount of component (B) was changed to 66.7 parts. The appearance of the release sheet thus obtained was observed, and the peel strength and residual adhesion rate were evaluated. These are shown in Table 1.
[0092] [Comparative Example 6] Comparative Composition 6 Comparative composition 6 was obtained in the same manner as in Example 1, except that 33.3 parts of (b-2) polydimethylsiloxane in which both molecular chain terminals are blocked with hexenyl groups and which has hexenyl groups on its side chains (viscosity 400 mPa s, content of vinyl (CH2=CH-) moieties in the hexenyl groups 0.97% by mass) was used as component (B) of composition 1 in Example 1. The appearance of the release sheet thus obtained was observed, and the peel strength and residual adhesion rate were evaluated. The results are shown in Table 1.
[0093] [Comparative Example 7] Comparative Composition 7 Comparative composition 7 was obtained in the same manner as in Example 1, except that the amount of component (A) used in Comparative composition 6 in Comparative Example 6 was changed to 50.0 parts and the amount of component (B) used was changed to 50.0 parts. The appearance of the release sheet thus obtained was observed, and the peel strength and residual adhesion rate were evaluated. These are shown in Table 1.
[0094] [Comparative Example 8] Comparative Composition 8 Comparative composition 8 was obtained in the same manner as in Example 1, except that the amount of component (A) in Comparative composition 6 was changed to 33.3 parts and the amount of component (B) was changed to 66.7 parts. The appearance of the release sheet thus obtained was observed, and the peel strength and residual adhesion rate were evaluated. The results are shown in Table 1.
[0095] [Comparative Example 9] Comparative Composition 9 Comparative composition 9 was obtained in the same manner as in Comparative Example 1, except that 66.7 parts of (a-2) polydimethylsiloxane (plasticity 1.50, vinyl content 0.75% by mass) in which both molecular chain terminals are blocked with vinyl groups and which has vinyl groups on the side chains was used as component (A) of comparative composition 1 in Comparative Example 1. The appearance of the release sheet thus obtained was observed, and the peel strength and residual adhesion rate were evaluated. The results are shown in Table 1.
[0096] [Comparative Example 10] Comparative Composition 10 Comparative composition 9 was obtained in the same manner as in Comparative Example 1, except that (a-3) polydimethylsiloxane (plasticity 1.50, vinyl content 0.85% by mass) in which both molecular chain terminals are blocked with methyl groups and which has vinyl groups on the side chains was used as component (A) of comparative composition 1 in Comparative Example 1. The appearance of the release sheet thus obtained was observed, and the peel strength and residual adhesion rate were evaluated. The results are shown in Table 1.
[0097] Table 1 shows a summary of the terminal and side chain functional groups of components (a-1) to (a-3), (b-1), and (b-2) when component (A) is represented by chemical formula (1) and component (B) is represented by chemical formula (3). [ka] [ka]
[0098] [Table 1]
[0099] As is clear from the results shown in Table 1, the release sheets obtained by curing the compositions (Examples 1 to 3) using a combination in which both components (A) and (B) have alkenyl groups only in the side chains, had excellent appearance, low peel resistance against adhesive substances, and good residual adhesion rate. On the other hand, the comparative experiments were carried out in which the components (A) and (B) of the present invention were not used in combination, or an organopolysiloxane having an alkenyl group other than the side chain was used as a raw material. However, in the comparative compositions 1, 3 to 10 (Comparative Examples 1 and 3 to 10), the peel resistance of the obtained release layer against adhesive substances was high, and good release properties could not be achieved. In the comparative composition 2 (Comparative Example 2) in which only component (B) was used, it was difficult to uniformly coat the composition on the substrate film, resulting in poor appearance of the release sheet, and practical coatability could not be achieved.
Claims
1. (A) a linear organopolysiloxane which is in a liquid state having a viscosity of 1,000,000 mPa·s or more at 25° C. or in a gum state having a plasticity at 25° C. and which has alkenyl groups having 2 to 12 carbon atoms only on the side chains of the molecule; (B) A linear organopolysiloxane having a viscosity of 1,000 mPa·s or less at 25°C and having alkenyl groups having 2 to 12 carbon atoms only on the side chains of the molecule. (C) an organohydrogenpolysiloxane having two or more silicon-bonded hydrogen atoms (Si—H) in one molecule, and (D) Hydrosilylation reaction catalyst The composition comprises The mass ratio of the component (A) to the component (B) {(A) / (B)} is in the range of 95 / 5 to 5 / 95, and The curable organopolysiloxane composition is a linear organopolysiloxane in which components (A) and (B) have alkenyl groups having 4 to 12 carbon atoms only on the side chains of the molecule, the content of vinyl (CH 2 ═CH—) moieties in the alkenyl groups is 0.5 to 3.0 mass %, and the molecular chain terminals are blocked with trialkylsilyl groups.
2. 2. The curable organopolysiloxane composition according to claim 1, wherein the mass ratio of component (A) to component (B) {(A) / (B)} is in the range of 90 / 10 to 10 / 90.
3. 3. The curable organopolysiloxane composition according to claim 1 or 2, further comprising (E) an organic solvent.
4. The curable organopolysiloxane composition according to any one of claims 1 to 3, further comprising (F) a hydrosilylation reaction inhibitor.
5. The curable organopolysiloxane composition according to any one of claims 1 to 4, further comprising (G) a photopolymerization initiator.
6. the mass ratio of component (A) to component (B) {(A) / (B)} is in the range of 70 / 30 to 30 / 70; 6. The curable organopolysiloxane composition according to any one of claims 1 to 5, wherein the molar ratio of SiH groups in component (C) to the total molar number of alkenyl groups in components (A) and (B) is 0.5 to 5.
7. A release coating agent comprising the curable organopolysiloxane composition according to any one of claims 1 to 6.
8. 7. A sheet-like article comprising a cured layer formed by curing the curable organopolysiloxane composition according to any one of claims 1 to 6 and a sheet-like substrate.
9. A laminate having a structure in which an adhesive layer is arranged opposite at least one release layer, the release layer being a release layer made of a cured product obtained by curing the release coating agent described in claim 7.
Citation Information
Patent Citations
Apparatus for cooling and heating air
JP1978028943A
Silicone composition for release paper
JP1986159480A
Organopolysiloxane composition capable of forming peelable film
JP1990145650A
Speaker unit
JP1991052498A
Organopolysiloxane composition for formation of releasable cured film
JP1993171047A